Bovine Viral Diarrhea in Cattle in Indonesia and its Problems - Sudarisman . (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
Bovine Viral Diarrhea (BVD) is a disease caused by the bovine viral diarrhea virus (BVDV), an ubiquitous, easily transmitted virus with worldwide distribution. The majority of postnatal infections with BVDV are nonclinical, with biphasic temperature elevation and leucopenia followed by a spesific immune response measurable by serum neutralisation test. The infection can be diagnosed serologically or virologically and the disease is recognized by clinical signs and pathological lesions. Disease control is based on the use of modified live virus (MLV) vaccines. Opinions vary on the relative economic importance of BVD, depends on the appropriateness and timing of vaccination in various production-management system. Key words: Bovine viral diarrhea, cattle, disease control, vaccine